RANCANG BANGUN SISTEM PENUNJANG KEPUTUSAN STRATEGI PENGEMBANGAN TRANSPORTASI LAUT PADA ERA GLOBALISASI (Design on Empowerment Strategic of National Sea Transport in Globalization Era) - Suyadi Cornellius; Daniel R. Monintja; Tommy H. Purwaka; Hartrisari Hardjomidjojo (Institut Pertanian Bogor, 2007)
The background of choosing this topics is to realize that unfavorable condition is occur in the national sea transports in which is a very weak competitiveness in having a cargoes share. Archipelagic state of Indonesia comprises 17,506 islands, has 5.8 million kilometers square of waters, and a large amount of market cargoes, however national armada just only can contribute a small number of national incomes, that marked by reaching only five percent share of the total export-import cargoes and only fifty percent share of the total domestics cargoes, in which the rest of them are occupied by foreign armada. Those are caused of the maritime sector income loss that in amount of U5D 18,4 millions yearly that consist of USD 12,4 millions in cargoes share and USD 6 millions in transhipment oportunities. The purpose of this study is to obtain the capability of Indonesian sea transport within globalization era by formulating a design the empowerment strategy to support decision making policy in sea transportation solving problem. The dilta are collected from interviewing and filling the polling by eighteen competence officers of the maritime stakeholders that come from three maritime institutions such as the regulator, the actors, and the users. SWOT analysis, computerized influence / dependence (I/D) matrix, and importance and performance analysis (IPA) methods are used for analyzed data. The results of this study is showed that the influence on and the dependency of the five key factors in technoware, the six key factors in humanware, the four key factors in infoware, and the five key factors in orgaware are founded to high, and should be developed. So that it needed some sufficiency......